2004
DOI: 10.1038/sj.emboj.7600289
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-null cells require PDGFR α signaling-mediated stromal fibroblast recruitment for tumorigenesis

Abstract: We generated VEGF‐null fibrosarcomas from VEGF‐loxP mouse embryonic fibroblasts to investigate the mechanisms of tumor escape after VEGF inactivation. These cells were found to be tumorigenic and angiogenic in vivo in spite of the absence of tumor‐derived VEGF. However, VEGF derived from host stroma was readily detected in the tumor mass and treatment with a newly developed anti‐VEGF monoclonal antibody substantially inhibited tumor growth. The functional significance of stroma‐derived VEGF indicates that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
185
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(194 citation statements)
references
References 56 publications
4
185
2
3
Order By: Relevance
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…PDGFs can influence cancer growth and malignant angiogenesis through several mechanisms, including the activation of PDGFRa expressed on cancer cells, stromal fibroblasts, and vascular endothelial cells and by PDGF-induced production of vascular endothelial growth factor (VEGF) by stromal cells. [45][46][47][48][49][50][51][52][53][54][55]57,60 The asterisk indicates that Table 1 required for the development of malignant stroma, 46 a separate study indicated that the induction of PDGF-CC expression in melanoma cells led to accelerated tumor growth through the activation of PDGFRa. 47 In the latter study, the exclusive expression of PDGFRa on cancerassociated stromal fibroblasts illuminated a paracrine mechanism of stromal-regulated melanoma tumor growth.…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…A common cellular component of both tissues is fibroblasts, which generate ECM components and paracrine factors (Kalluri and Zeisberg, 2006). In tumors, stromal fibroblasts as well as cancer cells are a significant source of VEGF promoting angiogenesis (Hlatky et al, 1994;Fukumura et al, 1998;Dong et al, 2004). Although the phenotypic changes in tumor fibroblasts are considered responsible for the angiogenic properties as distinct from those of normal fibroblasts (Orimo et al, 2005;Kalluri and Zeisberg, 2006), fibroblasts from normal tissues also produce VEGF (Berse et al, 1992;Hlatky et al, 1994).…”
Section: Introductionmentioning
confidence: 99%